Evaluating e-assessment: A practical application using statistical methods - Azevedo, José (2020)
The use of Information and Communication Technologies (ICT) in the assessment process is becoming an asset, giving rise to the so-called computer based assessment or e-assessment. Nowadays, its use is becoming more usual in Higher Education Institutions. Closed formats for questions, namely Multiple Choice, are the most commonly used. This chapter presents a literature review of the main aspects related to this topic, including the main modalities of assessment (Continuous Assessment, summative assessment and continuous assessment). Issues related to Multiple Choice Questions (MCQ) are discussed with more detail, referring to the various formats of MCQ, its advantages and limitations, with a particular focus on its use in mathematics tests. Also, some guidelines for the quality assurance of MCQ with quality are included.